STRATEGIC INSTRUCTIONAL LEADERSHIP OF THE SCHOOL PRINCIPAL THROUGH LANGUAGE IN ENHANCING TEACHER PROFESSIONALISM - Tiara Amanda; Inom Nasution (Esteem Journal of English Education Study Programme, 2025)
Teacher professionalism plays a crucial role in improving education quality, especially in madrasahs with unique cultural and organizational characteristics. This study explores the strategic instructional leadership of the principal at MTs Al-Wasliyah Deli Serdang, focusing on the use of language as a key tool to enhance teacher professionalism. Using a qualitative case study approach, data were gathered through interviews, observations, and documentation involving the principal, teachers, and students. The results show that the principal employed several language-driven leadership strategies, such as modeling professional communication, conducting supervision with constructive feedback, facilitating professional dialogue, and providing motivation through verbal encouragement and training. These strategies helped improve teacher competence and fostered a collaborative school culture. Challenges included low teacher motivation, heavy administrative tasks, limited resources, and lack of external support. To overcome these, the principal used a collaborative and adaptive leadership style, emphasizing effective use of language to inspire, communicate goals, and strengthen relationships. In conclusion, language-based instructional leadership is essential in shaping teacher professionalism. The strategic use of language enables principals to guide, support, and empower teachers, ultimately contributing to a more effective and supportive learning environment in madrasahs.